1988
DOI: 10.1111/j.1476-5381.1988.tb11504.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of vasopressor and vas deferens responses by α, β‐methylene ATP in the pithed rat

Abstract: 1 The pressor responses produced by the intravenous administration of a,#-methylene ATP were tachyphylactic.2 a,fi-Methylene ATP can attenuate pressor responses to sympathetic nerve stimulation both in the presence and in the absence of a-adrenoceptor blocking agents.3 a,#-Methylene ATP has no effect on the pressor responses produced by bolus injections of noradrenaline.4 In the presence of a-adrenoceptor blocking agents, a,x-methylene ATP further attenuates contractions of the vas deferens produced by nerve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 22 publications
4
33
1
Order By: Relevance
“…No NA release was detected upon nerve stimulation, and reserpine in the dosage used in this study is known to cause a marked (>90%) depletion of tissue NA in the pig (see Lundberg et al, 1990). The presumably non-adrenergic vascular effects of sympathetic stimulation in reserpine-treated pigs in the presence of a Y. receptor antagonist may therefore be caused by some rapidly acting and quickly metabolized transmitter, like ATP, especially at low frequency stimulation (von Kigelgen & Starke, 1985;Bulloch & McGrath, 1988). Rapid, presumably ATPmediated nerve stimulation-evoked contractions of isolated blood vessels in vitro thus remain after reserpine (Muramatsu, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…No NA release was detected upon nerve stimulation, and reserpine in the dosage used in this study is known to cause a marked (>90%) depletion of tissue NA in the pig (see Lundberg et al, 1990). The presumably non-adrenergic vascular effects of sympathetic stimulation in reserpine-treated pigs in the presence of a Y. receptor antagonist may therefore be caused by some rapidly acting and quickly metabolized transmitter, like ATP, especially at low frequency stimulation (von Kigelgen & Starke, 1985;Bulloch & McGrath, 1988). Rapid, presumably ATPmediated nerve stimulation-evoked contractions of isolated blood vessels in vitro thus remain after reserpine (Muramatsu, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…, 1988), but there are no pre vious reports on the "in vivo" effects of a,r3-methy lene-ATP. However, the vasoconstrictor action of this compound in the cerebral circulation is consis tent with the pressor response recorded during its intravascular administration in rats Bulloch and McGrath, 1988) and cats (Ribeiro and Lima, 1985).…”
Section: Discussionmentioning
confidence: 57%
“…More recently, it was found that a novel administration regime of mATP in the pithed rat avoided the cardiotoxic effects of the drug. This modified regime of administration of mATP reduced the sympathetic pressor response to spinal stimulation by 60% in the absence of xadrenoceptor blockade, and completely abolished the residual response after a-adrenoceptor antagonism (Bulloch & McGrath, 1988). The previous inability of mATP to affect the pressor response before a-antagonism, or to abolish the residual response after a-antagonism completely (Flavahan et al, 1985), was attributed to the transient nature of its action.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the effects of mATP and a-adrenoceptor antagonists appeared to be additive, and dissect the sympathetic pressor response of the pithed rat into a-adrenergic (40%) and purinergic (60%) components. The use of mATP was demonstrated to be selective in that it had no effect on the pressor response to intravenously administered NA (Bulloch & McGrath, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation